EFEKTIVITAS PENERAPAN BERBAGAI METODE RONDE KEPERAWATAN TERHADAP KINERJA PERAWAT DAN KEPUASAN PASIEN: LITERATURE REVIEW - Metilda, Metilda; Amelia, Kartika Ghina; Kartika, Nazwa Sapparingga Amalia; Maulani, Nabila Apriliana; Anggraeni, Nina (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
ABSTRACT Background: Nurse performance is a crucial aspect in improving the quality of health services. Nursing rounds, as a professional method, have been identified as an effective strategy for improving nursing care, patient satisfaction, and nurse performance. This study aims to analyze the impact of nursing rounds on the implementation of nursing care through a literature review of six selected articles. Method: This article uses a literature review method with article selection criteria based on relevance, peer-reviewed journal quality, maturity (2016–2025), strong methodology, and contribution to the field. Six articles were selected: four from Indonesia ((Astuti et al., 2021); (Meri et al., 2022); (Lastari & Kartika, 2023); (Setiawan et al., 2023)) and two international articles ((Mulugeta et al., 2020); (Wasfie & Heeter, 2025)). Data were collected from databases such as Google Scholar and PubMed, with a synthesis analysis of the findings. Results: Findings show that nursing rounds improve patient satisfaction (score increased from 71.02 to 79.69, p=0.001), nurse knowledge (from 51% to 68%), and team collaboration. Benefits include critical thinking, rapid diagnosis, better care plans, and thorough evaluation. Domestic articles focused on local training, while international ones emphasized clinical outcomes such as error reduction. Conclusion: Nursing rounds effectively improve nurse performance and care quality, with strong empirical support. Results: Findings indicate that nursing rounds improve patient satisfaction (score increased from 71.02 to 79.69, p=0.001), nurse knowledge (from 51% to 68%), and team collaboration. Benefits include critical thinking, rapid diagnosis, better care plans, and thorough evaluation. Domestic articles focus on local training, while international ones emphasize clinical outcomes such as error reduction. Conclusion: Nursing rounds effectively improve nurse performance and care quality, with strong empirical support. Round training is recommended for hospitals, with suggestions for technology integration, long-term evaluation, and comparative research for global adaptation ABSTRAK Latar Belakang: Kinerja perawat merupakan aspek krusial dalam meningkatkan kualitas pelayanan kesehatan. Ronde keperawatan, sebagai metode profesional, telah diidentifikasi sebagai strategi efektif untuk meningkatkan asuhan keperawatan, kepuasan pasien, dan kinerja perawat. Kajian ini bertujuan menganalisis dampak ronde keperawatan terhadap pelaksanaan asuhan keperawatan melalui literature review dari enam artikel terpilih. Metode: Artikel ini menggunakan metode literature review dengan kriteria pemilihan artikel berdasarkan relevansi, kualitas jurnal peer-reviewed, kedewasaan (2016–2025), metodologi kuat, dan kontribusi terhadap bidang. Enam artikel dipilih: empat dari Indonesia ((Astuti et al., 2021); (Meri et al., 2022); (Lastari & Kartika, 2023); (Setiawan et al., 2023)) dan dua internasional ((Mulugeta et al., 2020); (Wasfie & Heeter, 2025)). Data dikumpulkan dari database seperti Google Scholar dan PubMed, dengan analisis sintesis temuan. Hasil: Temuan menunjukkan ronde keperawatan meningkatkan kepuasan pasien (skor naik dari 71,02 menjadi 79,69, p=0,001), pengetahuan perawat (dari 51% menjadi 68%), dan kolaborasi tim. Manfaat meliputi pemikiran kritis, diagnosis cepat, rencana asuhan yang lebih baik, dan evaluasi teliti. Artikel dalam negeri fokus pada pelatihan lokal, sementara internasional menekankan hasil klinis seperti pengurangan kesalahan. Kesimpulan: Ronde keperawatan efektif meningkatkan kinerja perawat dan mutu asuhan, dengan dukungan empiris kuat. Pelatihan ronde direkomendasikan untuk rumah sakit, dengan saran integrasi teknologi, evaluasi jangka panjang, dan penelitian komparatif untuk adaptasi global.